Heat transfer from the working fluid in an air motor with a spool air distribution mechanism - Nikitchenko, I.; Trofimenko, D.; Abramchuk, F.; Нікітченко, Ігор Миколайович; Трофіменко, Дмитро Олександрович; Абрамчук, Федір Іванович (Харківський національний автомобільно-дорожній університет, 2025)
Heat transfer processes from the working fluid to the cylinder walls in heat engines play an important role. First, the thermal state of engine components, which determines operational reliability, depends on the parameters of the working fluid and on the intensity of heat transfer. Second, heat transfer from the working fluid represents a loss of thermal energy, which always reduces the conversion of the working fluid energy into useful work. Therefore, during engine design as well as during its improvement, reliable methods for calculating heat transfer from the working fluid to the cylinder walls are required. Purpose. The aim of this study is to improve the method for calculating heat transfer from the working fluid to the walls, taking into account the design features of a pneumatic motor, and to determine the amount of heat loss that could otherwise be converted into useful work. Methodology. It is proposed to study heat transfer separately in the pneumatic motor cylinder and in the channel connecting the spool valve with the cylinder. This approach makes it possible to account for significant heat losses in the channels and to confirm them using Joule’s law. Results. Processing of experimental p-V diagrams of the pneumatic motor made it possible to obtain the magnitude of heat losses in the channels connecting the spool valve with the cylinder and to identify ways to reduce them. An evaluation of the relationships governing heat transfer in the pneumatic motor cylinder was carried out. Originality. The proposed approach enables reliable separate determination of the heat transferred from the working fluid in the pneumatic motor cylinder and in its channels. Practical value. The obtained results make it possible to identify ways to improve the pneumatic motor design. To reduce heat losses, the channel length should be minimized, and when using a valve-type air distribution system, the channels should be eliminated altogether.
Тепловіддача від робочого тіла у пневмодвигуні із золотниковим механізмом розподілу повітря
Keywords: convective heat transfer; heat transfer coefficient; pneumatic motor; heat losses; compressed air; Joule’s law; thermal balance; конвективна тепловіддача; коефіцієнт тепловіддачі; пневмодвигун; втрати теплоти; стиснене повітря; закон Джоуля; тепловий баланс; 641.43; 10.30977/AT.2219-8342.2025.57.0.05